William James's pluralism : an antidote for contemporary extremism and absolutism - Viney, Wayne (New York, NY : Routledge, 2022)
"William James's Pluralism: An Antidote for Contemporary Extremism and Absolutism explores extremism and the related problem of absolutism in the context of the psychology and philosophy of William James"--
The most pregnant of all the dilemmas of philosophy -- William James and the tensions between the one and the many -- Moral monism and pluralism -- Methodological singularities -- The single cause : God, free will, and the reflex -- Ontological monism -- James quarrels with monism as he embraces pluralism.
Keywords: James, William, -- 1842-1910.; Pluralism; Monism; Philosophy, American -- 19th century; PSYCHOLOGY / History